Sustainable Approaches to Alleviate Heavy Metal Stress in Tomatoes: Exploring the Role of Chitosan and Nanosilver - Marcelina Krupa-Małkiewicz; Ireneusz Ochmian (Agronomy)
This study investigates the impact of copper (Cu) stress on tomato plants (Solanum pimpinellifolium) and explores the potential of chitosan and nanosilver (nAg) in mitigating its effects. Copper, while essential for plant growth, can be toxic at elevated levels, leading to oxidative stress and reduced plant productivity. This research focuses on determining how chitosan and nAg treatments influence plant growth, fruit yield, and biochemical responses under Cu-induced stress. A greenhouse experiment was conducted, where tomato plants were treated with Cu, chitosan, nAg, and their combinations. The results revealed that chitosan improved root growth, and enhanced antioxidant properties, including increased ascorbic acid and lycopene content. Nanosilver treatments, while reducing shoot growth, significantly increased fruit yield and potassium uptake. The combination of Cu with chitosan or nAg provided synergistic benefits, improving plant resilience and fruit quality. Specifically, copper+chitosan (Cu+Ch) increased dry matter and delayed ripening, while Cu+nAg enhanced potassium uptake and overall fruit yield. Additionally, Cu accelerated the ripening of tomatoes. These findings suggest that chitosan and nanosilver are effective strategies to mitigate copper toxicity in tomato plants, offering a sustainable approach to improve crop productivity and quality under heavy metal stress conditions.